Effect of integrated traditional Chinese and Western medicine nursing management model in relieving constipation of deficiency syndrome in cancer patients (中西医结合护理管理模式改善肿瘤患者虚证便秘效果观察) - LIU Yin (柳吟); HUANG Jun (黄君) (中西医结合护理)
Objective To observe the effect of the integrated traditional Chinese and Western medicine nursing management model in relieving constipation of deficiency syndrome in cancer patients. Methods A total of 60 cancer patients with constipation of deficiency syndrome were selected as the research objects, and they were divided into control group and observation group according to hospital admission time, with 30 cases in each group. The control group was given routine nursing, and the observation group was treated with traditional Chinese and Western medicine on the basis of conventional treatment and nursing. The constipation condition, treatment efficacy, patients’ mental status and quality of life were evaluated and compared between two groups. Results The constipation symptom score in the observation group was lower than that in the control group(P＜0. 05). The total effective rates of the observation group and the control group were 93. 33%(28/30) and 73. 33%(22/30), respectively, and the efficacy of the observation group was better than that of the control group (P＜0. 05). The Self-rating Depression Scale and Self-rating Anxiety Scale scores in the observation group were significantly lower than those in the control group (P＜0. 05). According to the Short- Form 36 (SF-36) questionnaire, the quality of life of the observation group was significantly improved compared with that of the control group (P＜0. 05). Conclusion The comprehensive nursing management mode of integrated traditional Chinese and Western medicine can effectively improve the health status and quality of life of cancer patients with constipation of deficiency syndrome, which is worthy of clinical promotion. (目的 探讨中西医结合护理管理模式改善肿瘤患者虚证便秘的效果。方法 将60例肿瘤虚证便秘患者根据入院时间分为观察组和对照组, 各30例。对照组给予常规护理, 观察组在对照组基础上开展中西医结合护理干预。评价两组便秘症状改善情况、总疗效、心理状态以及生活质量。结果 观察组便秘症状评分均低于对照组, 差异有统计学意义(P＜0. 05); 观察组疗效评估总有效率93. 33%(28/30), 高于对照组的73. 33%(22/30), 差异有统计学意义(P＜0. 05); 观察组焦虑自评量表(SAS)及抑郁自评表(SDS)评分低于对照组, 差异有统计学意义(P＜0. 05); 观察组简明生活质量量表(SF-36)量表各维度评分均高于对照组, 差异有统计学意义(P＜0. 05)。结论 中西医结合护理干预能有效改善肿瘤患者虚证便秘症状, 减轻负性情绪, 提高患者生活质量。)